Crosslinking of membrane CD13 in human neutrophils mediates phagocytosis and production of reactive oxygen species, neutrophil extracellular traps and proinflammatory cytokines - Pérez-Figueroa, Erandi; Álvarez-Carrasco, Pablo; Ortega, Enrique (Frontiers in Immunology, 2022)
Aminopeptidase N, or CD13, is a cell membrane ectopeptidase highly expressed in myeloid cells. Through its enzymatic activity, CD13 regulates the activity of several bioactive peptides, such as endorphins and enkephalins, chemotactic peptides like MCP-1 and IL-8, angiotensin III, bradikinin, etc. In recent years, it has been appreciated that independently of its peptidase activity, CD13 can activate signal transduction pathways and mediate effector functions such as phagocytosis and cytokine secretion in monocytes and macrophages. Although neutrophils are known to express CD13 on its membrane, it is currently unknown if CD13 can mediate effector functions in these cells. Here, we show that in human neutrophils CD13 can mediate phagocytosis, which is dependent on a signaling pathway that involves Syk, and PI3K. Phagocytosis mediated by CD13 is associated with production of reactive oxygen species (ROS). The level of phagocytosis and ROS production mediated by CD13 are similar to those mediated through FcγRIII (CD16b), a widely studied receptor of human neutrophils. Also, CD13 ligation induces the release of neutrophil extracellular traps (NETs) as well as cytokine secretion from neutrophils. These results support the hypothesis that CD13 is a membrane receptor able to activate effector functions in human neutrophils.